2022
DOI: 10.1051/0004-6361/202142533
|View full text |Cite
|
Sign up to set email alerts
|

Strong spiral arms drive secular growth of pseudo bulges in disk galaxies

Abstract: Spiral-driven instabilities may drive gas inflow to enhance central star formation in disk galaxies. We investigate this hypothesis using the Sloan Digital Sky Survey (SDSS) in a sample of 2779 nearby unbarred star-forming main sequence spiral galaxies. The strength of spiral arms is quantified by their average Fourier amplitude relative to the axisymmetric disk. The star formation properties in the central 1–3 kpc region were derived from the SDSS spectra. We show that galaxies with stronger spiral arms not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 161 publications
0
6
0
Order By: Relevance
“…The spiral arms themselves might help enhance the concentration of the galaxy by driving gas inwards (Kim & Kim 2014) and triggering central star formation. Galaxies with strong arms are more likely to have enhanced sSFR in the central region (Yu et al 2022), supporting this idea. Stars can also migrate radially within a galaxy disk due to resonances with spiral arms or bars, or interactions with massive clumps, but this affects the outer disk more than the central regions (Sellwood & Binney 2002;Minchev et al 2012;Wu et al 2020;Lian et al 2022).…”
Section: Arm Strengths and Quenching In Cluster Spirals Versus Field ...mentioning
confidence: 61%
See 1 more Smart Citation
“…The spiral arms themselves might help enhance the concentration of the galaxy by driving gas inwards (Kim & Kim 2014) and triggering central star formation. Galaxies with strong arms are more likely to have enhanced sSFR in the central region (Yu et al 2022), supporting this idea. Stars can also migrate radially within a galaxy disk due to resonances with spiral arms or bars, or interactions with massive clumps, but this affects the outer disk more than the central regions (Sellwood & Binney 2002;Minchev et al 2012;Wu et al 2020;Lian et al 2022).…”
Section: Arm Strengths and Quenching In Cluster Spirals Versus Field ...mentioning
confidence: 61%
“…A number of mechanisms have been suggested that may enhance the relative brightness of the spheroidal component of a galaxy relative to its disk. These include (1) minor mergers (Bekki 1998;Aguerri et al 2001;Bournaud et al 2005;Parry et al 2009;Hopkins et al 2010), (2) gas-rich major mergers (Springel & Hernquist 2005;Robertson et al 2006;Hopkins et al 2009;Athanassoula et al 2016;Sparre & Springel 2017), (3) central star formation triggered by inflowing gas driven by galaxy interactions (Moss & Whittle 2000;Smith et al 2007;Li et al 2008), bars (Pfenniger & Norman 1990), and/or spiral arms (Kim & Kim 2014;Yu et al 2022), (4) fading of the disk due to quenching (Weinmann et al 2009;Carollo et al 2016), (5) tidal heating of a disk in the gravitational field of a cluster (Gnedin 2003;Goshi et al 2020), or (6) tidal stripping of stars from the outer disks of galaxies in clusters by fast interactions with multiple neighbors ("harrassment;" Moore et al 1996Moore et al , 1998Moore et al , 1999 or from the tidal effect of the cluster as a whole (Byrd & Valtonen 1990;Gnedin 2003;Aguerri et al 2004;Łokas 2020).…”
Section: Morphology Quenching and Environmentmentioning
confidence: 99%
“…It is necessary to explore the co-evolution of spiral arms and bars, which is particularly important in the presence of gas. Namely, strong spiral arms can also drive gas inflow to the centre as recently demonstrated by Yu et al (2022), which can lead to additional enhancement of the central star formation and the build-up of pseudo-bulges or faster bar growth.…”
Section: The Observability Of These Barsmentioning
confidence: 84%
“…The higher central molecular gas concentration observed in local barred spiral galaxies (Kuno et al 2007;Yu et al 2022a) provides direct evidence for bardriven gas inflow, and Yu et al (2022a) also suggest the spiral arms can playing a role in transporting gas to the center. On the other hand, barred galaxies with suppressed central SFR often exhibit weak to nearly vanished spiral arms (Wang et al 2020;Yu et al 2022b). J0107a possesses a strong stellar bar and pronounced spiral arms, and the high SFR may be triggered by gas inflow driven by stellar structures in its gas-rich disk.…”
Section: Discussionmentioning
confidence: 99%